2010
DOI: 10.1093/sleep/33.10.1349
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Cardiovascular Tests in Children with Obstructive Sleep Apnea Syndrome

Abstract: Our data point to an increase in basal sympathetic activity during wakefulness and to an impaired reaction to several physiological stimuli, which is dependent on the severity of OSAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 48 publications
3
28
0
2
Order By: Relevance
“…In recent years, OSA has emerged as a chronic low-grade inflammatory disease (15), and increasing evidence supports a causative link between pediatric OSA and cardiovascular diseases (CVD), including hypertension, endothelial dysfunction, and atherosclerosis (615). …”
mentioning
confidence: 99%
“…In recent years, OSA has emerged as a chronic low-grade inflammatory disease (15), and increasing evidence supports a causative link between pediatric OSA and cardiovascular diseases (CVD), including hypertension, endothelial dysfunction, and atherosclerosis (615). …”
mentioning
confidence: 99%
“…The most accepted explanation proposes that chronic intermittent hypoxia produces oxidative stress, inflammation, and sympathetic hyperactivity, which led to endothelial dysfunction and hypertension [19,25,28,41,43,52,53,65,99,100], but it is likely that intrathoracic pressure changes causing excessive mechanical stress on large artery walls and the heart, and arousal-induced sympathetic hyperactivity may also contribute to the endothelial dysfunction [47]. OSA is characterized by repeated episodes of total or partial airflow detention during sleep produced by the pharyngeal collapse, eliciting intermittent hypoxia and hypercapnia, negative intrathoraxic pressure, sleep fragmentation and arousal.…”
Section: Pathogenic Mechanisms Of the Hypertension Induced By Osamentioning
confidence: 99%
“…Reactive oxygen species (ROS) and reactive nitrogen species (RNS), and pro-inflammatory agents have been proposed as mediators of cardiovascular and cognitive alterations in OSA patients [7,13,33,45,52,65,102] and animal models [10, 15-18, 44, 48, 82, 84, 106]. Studies performed in OSA patients and animals exposed to intermittent hypoxia showed that the hypoxia-reoxygenation episodes produce systemic oxidative stress due to the accumulation of ROS and RNS, which are potential sources of cellular damage.…”
Section: Mediators Of Enhanced Carotid Body Chemosensory Responses Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, early detection of ANS abnormalities in children with untreated OSA may help to identify candidates who are at increased risk for developing morbidity, and thus provide them with timely and effective treatment. To this effect, alterations in ANS have been evaluated using different methodologies including heart rate variability (HRV), blood pressure (BP) and blood pressure variability (BPV) peripheral arterial tonometry, and catecholamine assays (12-16). However, a simple office-based test would be highly desirable.…”
Section: Introductionmentioning
confidence: 99%